The career effects of labour market conditions at entry - Dan Andrews; Nathan Deutscher; Jonathan Hambur; David Hansell (The Australian Government, The Treasury, 2020)
This paper explores the effects of labour market conditions at graduation on an individual's work-life over the following decade. Australians graduating into a state and year with a 5 percentage point higher youth unemployment rate can expect to earn roughly 8 per cent less in their first year of work and 3 per cent less after five years, with the effect gradually fading to around zero ten years on. The magnitude of this effect varies according to the characteristics of the individual and the tertiary institution they attend. We then explore the mechanisms behind this scarring. Scarring partly reflects the subsequent evolution of the unemployment rate - the fact that unemployment shocks tend to persist - highlighting the potential for timely and effective macroeconomic stabilisation policies to ameliorate these scarring effects. More generally, job switching to more productive firms emerges as a key channel through which workers recover from adverse shocks that initially disrupt (worker-firm) match quality. We find some evidence that the speed of recovery has slowed since 2000, which is consistent with the decline in labour market dynamism observed in Australia over that period.
Keywords: E24; J62; J64; 330; Wages; job mobility; job search